2013
DOI: 10.1371/journal.pone.0068698
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital Chlamydia trachomatis Infections among Ethnic Groups in Paramaribo, Suriname; Determinants and Ethnic Sexual Mixing Patterns

Abstract: BackgroundLittle is known about the epidemiology of urogenital Chlamydia trachomatis infection (chlamydia) in Suriname. Suriname is a society composed of many ethnic groups, such as Creoles, Maroons, Hindustani, Javanese, Chinese, Caucasians, and indigenous Amerindians. We estimated determinants for chlamydia, including the role of ethnicity, and identified transmission patterns and ethnic sexual networks among clients of two clinics in Paramaribo, Suriname.MethodsParticipants were recruited at two sites a sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Participants had been recruited at two sites in Paramaribo, Suriname, as part of a previous study9: The Dermatological Service, an integrated outpatient sexually transmitted infections (STI) clinic frequented by men and women, offering free-of-charge examination and treatment of STIs and infectious skin diseases. All women who visited for a STI check-up were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants had been recruited at two sites in Paramaribo, Suriname, as part of a previous study9: The Dermatological Service, an integrated outpatient sexually transmitted infections (STI) clinic frequented by men and women, offering free-of-charge examination and treatment of STIs and infectious skin diseases. All women who visited for a STI check-up were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that the prevalence of Chlamydia trachomatis differed between ethnic groups in Suriname 9. The same might be true for the prevalence of carcinogenic HPV infection, as ethnic disparities in the prevalence of premalignant cervical lesions have been described 10.…”
Section: Introductionmentioning
confidence: 97%
“…The third scheme was developed by Klint et al (10); it is intended for short-term clinical epidemiology and outbreak investigations and is based on five highly variable genomic loci (hctB [CT046], CT058, CT144, CT172, and pbpB [CT682]). The MLST scheme has been slightly modified to facilitate rational processing with only 1% loss of discriminatory capacity (13), and the current setup can be found at the Uppsala University C. trachomatis MLST database (http: //mlstdb.bmc.uu.se).Since its development in 2007, the scheme has been applied to a variety of clinical specimens, including samples from cases of urogenital chlamydia (7,(13)(14)(15)(16)(17)(18)(19)(20)(21), LGV (22,23), and trachoma (24). It has been useful for different purposes: (i) identification of clonal spread of LGV (22) …”
mentioning
confidence: 99%
“…Since its development in 2007, the scheme has been applied to a variety of clinical specimens, including samples from cases of urogenital chlamydia (7,(13)(14)(15)(16)(17)(18)(19)(20)(21), LGV (22,23), and trachoma (24). It has been useful for different purposes: (i) identification of clonal spread of LGV (22) …”
mentioning
confidence: 99%
See 1 more Smart Citation